A STUDY ON STUDENTS' MOTIVATION TOWARDS LEARNING ENGLISH LANGUAGE - Irza Yuzulia (Eltin Journal : Journal of English Language Teaching in Indonesia, 2021)
Motivation is the main point to determine the students’ desire to learn English. Students’ motivation will be correlated with their performance and achievement during the learning process. The research aimed to find out students’ motivations in learning English and the kinds of motivations they have. The respondents of this study were sixty two third-grader students of senior high school in Pekanbaru. In order to cope with the purposes of the research, this study used qualitative case study design. The data in this study was collected through questionnaire that consists of twenty-five questions and open-ended questions. The answers of the respondents were analyzed descriptively. Based on the result of the study, it is found that the students have high motivation to learn English. They are two types of motivation possessed by the respondents.  Related to Instrinsic motivation, the data showed that  they always attend the English class on time (88.1%), they need to be able to master English (95.2%), and usually learn English in my free time (69%). While, regarding the extrinsic motivation, the data revealed that students’ motivation in learning English due to several reasons such as to answer English tasks correctly (88.1%), to pass National Examination (80.9%), the teacher as the biggest inspiration to learn English (69%) and English will be beneficial for their future career (92.81%). Keywords: Motivation, EFL, English Learning.